Should translations be assessed holistically or through error analysis? - Waddington, Christopher (HERMES - Journal of Language and Communication in Business, 2001)
Teachers of translation use a variety of methods to evaluate their students’ translations. This paper discusses two kinds of methods typically used at European universities, those based on error analysis and those based on a holistic approach. With the results of the research carried out for his Ph.D. thesis, the author examines the quality of these ap-proaches and suggests possible improvements in the assessment of student translations.